-10=-7u+3(u-2)

Simple and best practice solution for -10=-7u+3(u-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10=-7u+3(u-2) equation:


Simplifying
-10 = -7u + 3(u + -2)

Reorder the terms:
-10 = -7u + 3(-2 + u)
-10 = -7u + (-2 * 3 + u * 3)
-10 = -7u + (-6 + 3u)

Reorder the terms:
-10 = -6 + -7u + 3u

Combine like terms: -7u + 3u = -4u
-10 = -6 + -4u

Solving
-10 = -6 + -4u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '4u' to each side of the equation.
-10 + 4u = -6 + -4u + 4u

Combine like terms: -4u + 4u = 0
-10 + 4u = -6 + 0
-10 + 4u = -6

Add '10' to each side of the equation.
-10 + 10 + 4u = -6 + 10

Combine like terms: -10 + 10 = 0
0 + 4u = -6 + 10
4u = -6 + 10

Combine like terms: -6 + 10 = 4
4u = 4

Divide each side by '4'.
u = 1

Simplifying
u = 1

See similar equations:

| 10-3f=-4f | | -(1+n)=-5n+5(1+2n) | | x^2-2xy+3x-6y=0 | | (-3w)=-10-4w | | 3x-32=-7x+5 | | 2x-8=-32 | | 5x^3+6x^2=0 | | (-5-6i)(7+8i)= | | 30u+4=10 | | b-9=4b | | g=3x-(2+x)(4x-3) | | 497*x=-20 | | 7(2x+14)=210 | | 3x+6=2(3x+12) | | -5+2a=3a+2 | | 42-4y=3y | | 64+4y=3y | | 5(2.95-a)=47.75 | | -(x-8)=2(x-6)+10 | | 140+10x=20+12x+x^2 | | 64+7u=15u | | (-2x+9)=0 | | 3(j+5)=(11-j) | | 9x^4+3x^3=0 | | 7x+499= | | (.5x-5)=0 | | 3u=28-u | | 2ab+4c= | | (N)=3-2n | | 5[6-(-2x-6)]=54x+126 | | 12x+6x-14=20 | | (4u)=(5)+u |

Equations solver categories